Surface Characteristics and Biofilm Development on Selected Dental Ceramic Materials - Kyoung H. Kim; Carolina Loch; J. Neil Waddell; Geoffrey Tompkins; Donald Schwass (International Journal of Dentistry)
Background. Intraoral adjustment and polishing of dental ceramics often affect their surface characteristics, promoting increased roughness and consequent biofilm growth. This study correlated surface roughness to biofilm development with four commercially available ceramic materials. Methods. Four ceramic materials (Vita Enamic®, Lava™ Ultimate, Vitablocs Mark II, and Wieland Reflex®) were prepared as per manufacturer instructions. Seventeen specimens of each material were adjusted and polished to simulate clinical intraoral procedures and another seventeen remained unaltered. Specimens were analysed by SEM imaging, confocal microscopy, and crystal violet assay. Results. SEM images showed more irregular surface topography in adjusted specimens than their respective controls. Surface roughness (Ra) values were greater in all materials following adjustments. All adjusted materials with the exception of Vitablocs Mark II promoted significantly greater biofilm growth relative to controls. Conclusion. Simulated intraoral polishing methods resulted in greater surface roughness and increased biofilm accumulation.